“XENOPHOBIC TIMES: MUSLIM SOMALI DIASPORA AND THE NATURE OF HUMAN RIGHTS, CULTURE, AND IDENTITY IN THE USA” - Coy, Tamara (PEOPLE: International Journal of Social Sciences, 2017)
The current political climate in Washington DC signals an apparent shift to a more Xenophobia stance. The latest treatment of refugees appears regressive, negating the UN’s 1951 Refugee Convention and its subsequent 1967 Protocol, raising the question of what constitutes human rights for refugees and transnational persons. Subsequently, how does this impact USA Refugees, particularly Muslim Somali women and children, and the way in which their identities are constructed and scrutinized by a Xenophobic climate?Through personal interviews and video footage, I explore how Muslim refugee women, like Ishtar and Saharo, who are often hidden female faces in the Somali Diaspora, assimilate and adjust to a predominantly white, Christian Bible belt community, whilst still maintaining their culture and identity in their widening Diaspora. I observe how the evangelical element of protestant religions in the Bible Belt region of Kentucky (KY) appear to offer a surprising bridge to both Christian and Islamic refugees alike, with shared values and conservative social foundations providing common ground. This ultimately demonstrates an unexpected tolerance in this region and the possible “hybridity” of cultural values.